Kunst van heden in België - Oostende. (Oostende : Casino Kursaal, 1965)
Aebly, Albert ; Alechinsky, Pierre ; Anthoons, Willy ; Antoine, Paul ; Arnould, Marcel ; Baibay, Gilbert ; Beirens, Vic ; Billet, Yves ; Boel, Maurice ; Bosschem, Willy ; Brankart, Silvin ; Burssns, Jan ; Bury, Pol ; Camus, Gustave ; Collignon, George ; Comhaire, Georges ; Creuz, Serge ; De Boeck, Felix ; de Grave, Jean-Jacques ; Delahaut, Jo ; Delvaux, Paul ; De Maeyer, Jacky ; de Montpellier, Béatrice ; Denaeyer, Roland ; etc.
Kunst van heden in België - Oostende, Casino Kursaal, Oostende, 26 juni - 1 augustus 1965
boek